2007
DOI: 10.1016/j.pec.2006.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a structured course involving goal management training in older adults: A randomised controlled trial

Abstract: Objective-The objective of this study was to investigate the effects of a structured 6-week neuropsychological course on the executive functioning of older adults with cognitive complaints.Methods-A randomised controlled design was used involving 69 community dwelling individuals aged 55 years and older. Both objective and subjective measures were included to assess executive functioning. General linear model with repeated measures analysis of variance was used to examine the intervention effects.Results-After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 40 publications
3
89
0
2
Order By: Relevance
“…Thus these findings suggest that overall participants' ability for deeper encoding of information through gist reasoning improved with training. Such training related gains extend previous findings of benefits from strategy training studies in normally aging seniors (Ball et al, 2002;Levine et al, 2007;van Hooren et al, 2007) to higher-order cognitive function such as gist reasoning, a skill shown to be essential to everyday life function (Adams et al, 1990;Ulatowska and Chapman, 1994;Meyer and Poon, 2001).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus these findings suggest that overall participants' ability for deeper encoding of information through gist reasoning improved with training. Such training related gains extend previous findings of benefits from strategy training studies in normally aging seniors (Ball et al, 2002;Levine et al, 2007;van Hooren et al, 2007) to higher-order cognitive function such as gist reasoning, a skill shown to be essential to everyday life function (Adams et al, 1990;Ulatowska and Chapman, 1994;Meyer and Poon, 2001).…”
Section: Discussionsupporting
confidence: 80%
“…Studies with training that targeted reasoning and problem solving in seniors have shown positive changes on self-reported measures such as activities of daily living, anxiety levels, etc. (Willis et al, 2006;Levine et al, 2007;van Hooren et al, 2007). For example, training that targets gist reasoning, defined as the ability to derive global meaning from explicit details, has been shown to improve meaning abstraction and other executive functions such as inhibition and working memory in clinical populations such as those with brain injury (Vas et al, 2009(Vas et al, , 2010, stroke (Ulatowska and Chapman, 1989), and attention deficit hyperactivity disorder (Gamino et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados mostraram que, depois da intervenção, os participantes do grupo de treino coletivo mostraram mais estabilidade, menos sentimentos de ansiedade e de estresse sobre o funcionamento da memória. Da mesma forma, Hooren et al (2007) verificaram que, após o treino coletivo, os participantes do GE se mostraram mais hábeis para administrar suas falhas executivas e apresentaram menos sintomas de ansiedade em relação ao GC. Ball et al (2002) avaliaram a efetividade e a durabilidade de três intervenções cognitivas distintas (treino de memória, treino de argumentação e treino de velocidade de processamento), com dez sessões cada, sobre o desempenho de idosos saudáveis em habilidades cognitivas e em atividades instrumentais de vida diária (AIVDs).…”
unclassified
“…However, only four of the patients included in this study were diagnosed with TBI, with no report of their severity level [15]. Yet, GMT has been shown to be efficacious in other populations including elderly and abstinent polysubstance abusers [16][17][18]. Levine et al speculated from their initial study that patients with mTBI might benefit from GMT more than patients with severe TBI because of their ability to better utilize learned strategies [9].…”
Section: Introductionmentioning
confidence: 94%